Long-Term Outcomes of Retinal Detachment in Phakic Eyes After Implantation of Implantable Collamer Lens V4c for High Myopia Correction - Xu, Weiwei; Song, Zhou; Huang, Yifei; Tao, Ye; Wang, Junqing; Wang, Liqiang; Li, Zhaohui (Frontiers in Medicine, 2020)
Aim: To estimate whether implantable collamer lens (V4c ICL) implantation increases the risk of retinal detachment in high myopia comparing with myopes with Rigid Gas-Permeable (RGP) correction. Methods: This prospective study was comprised of ICL group (704 eyes) and RGP group (628 eyes). Patients were enrolled according with inclusion criteria and exclusion criteria, then divided into ICL group and RGP group. Patients in ICL and RGP group received V4c ICL implantation and RGP fitting respectively. Retinal details, spherical equivalent refraction (SE), uncorrected distance visual acuity (UDVA), corrected distance vision acutivity (CDVA), axis length (AL), anterior chamber depth (ACD) and other relevant parameters were recorded at different time point. RRD morbidity and incidence, RRD morphology and relevant parameters were analyzed. Results: All enrolled patients were followed for 3 to 6 years. Patients characteristics before refractive procedure did not show statistical difference. At the end of follow up, all the RD cases were rhegmatogenous retinal detachment (RRD). The RRD morbidity of ICL group and RGP group was 1.99% (14 eyes) and 0.96% (6 eyes) respectively, which did not show statistical difference (P=0.12). During the first year after refractive procedure, the RRD incidence of ICL group was 0.85% (6/704), while this number of RGP group was 0.16% (1/628). It did not show statistical difference (P=0.08). Conclusion: Compared with RGP fitting, V4c ICL implantation for high myopia correction does not add RRD risk in long time. V4c ICL implantation is a safe method for high myopia correction.